Stratigraphic division and sedimentary facies of the Kathmandu Basin Group, central Nepal - Sakai, Harutaka (Journal of Nepal Geological Society, 2001)
On the basis of core drillings for academic purpose and surface geological survey in the Kathmandu Basin, I propose separate stratigraphic schemes of the basin-fill sediments for the southern, central and northern part of the basin. In the south, the late Pliocene to Pleistocene Kathmandu Basin Group is divided into three formations: the Tarebhir, redefined Lukundol and Itaiti Formation in ascending order. The Tarebhir Formation is mainly composed of fluvial gravel and sand beds deposited by the Proto-Bagmati River. The Lukundol Formation is mainly comprised of carbonaceous muddy sediments showing their deposition in marginal shallow lake environments. The uppermost fluvial sandy beds of the Lukundol Formation are overlain by boulder beds of alluvial fan deposit, which was newly named as the ltaiti Formation. The continuous drill core and previous drill data obtained from the central part of the basin has allowed to lithologically divide the sediments into three: the Bagmati, Kalimati and Patan Formation from bottom to top, respectively. The Bagmati Formation is the northern continuation of the Tarebhir Formation, and overlain by the 200 to 400 m thick lacustrine Kalimati Formation. The basal part is characterized by lignite and bituminous pebbly mudstone beds, which is named as the Basal Lignite Member. On the other hand, in the north and central parts, sand dominant lacustrine delta deposits called the Gokarna and Thimi formations are accumulated over the Kalimati Formation. In the central part of the valley, both Kalimati and Thimi formations are disconformably overlain by the mainly fluvial Patan Formation. The Palaeo- Kathmandu Lake has existed since 2.8 Ma in the central part of the Kathmandu Valley, and it was existing till about 10 kyr B.P. after which it finally drained out. However, in the south, there are no open lacustrine deposits, and marginal lacustrine deposits of the Lukundol Formation were directly overlain by alluvial fan deposits spread over the northern slope of the Mahabharat Lekh.